An Activity‐Based Probe Targeting Non‐Catalytic, Highly Conserved Amino Acid Residues within Bromodomains. (27th December 2018) - D'Ascenzio, Melissa; Pugh, Kathryn M.; Konietzny, Rebecca; Berridge, Georgina; Tallant, Cynthia; Hashem, Shaima; Monteiro, Octovia; Thomas, Jason R.; Schirle, Markus; Knapp, Stefan; Marsden, Brian; Fedorov, Oleg; et al.
Abstract: Bromodomain‐containing proteins are epigenetic modulators involved in a wide range of cellular processes, from recruitment of transcription factors to pathological disruption of gene regulation and cancer development. Since the druggability of these acetyl‐lysine reader domains was established, efforts were made to develop potent and selective inhibitors across the entire family. Here we report the development of a small molecule‐based approach to covalently modify recombinant and endogenous bromodomain‐containing proteins by targeting a conserved lysine and a tyrosine residue in the variable ZA or BC loops. Moreover, the addition of a reporter tag allowed in‐gel visualization and pull‐down of the desired bromodomains.